Genetic variation of FcγRIIa induces higher uptake of Leishmania infantum and modulates cytokine production by adherent mononuclear cells in vitro - Catarino, Jonatas da Silva; Oliveira, Rafael Faria de; Silva, Marcos Vinicius; Sales-Campos, Helioswilton; de Vito, Fernanda Bernadelli; Silva, Djalma Alexandre Alves da; Naves, Lucila Langoni; Oliveira, Carlo José Freire; Rodrigues, Denise Bertulucci Rocha; Rodrigues, Virmondes (Frontiers in Immunology, 2024)
Introduction Single nucleotide variations (SNVs) are specific genetic variations that commonly occur in a population and often do not manifest phenotypically. However, depending on their location and the type of nucleotide exchanged, an SNV can alter or inhibit the function of the gene in which it occurs. Immunoglobulin G (IgG) receptor genes have exhibited several polymorphisms, including rs1801274, which is found in the FcgRIIa gene. The replacement of A with T results in a Histidine (H) to Arginine (R) substitution, altering the affinity of the IgG receptor for IgG subtypes and C-reactive protein (CRP). In this study, we analyzed rs1801274 and its functional implications concerning L. Infantum uptake and cytokine production. Methods We genotyped 201 individuals from an endemic area for visceral leishmaniasis to assess the presence of rs1801274 using Taqman probes for a candidate gene study. Additionally, we included seventy individuals from a non-endemic area for a functional study. Subsequently, we isolated and cultivated one-week adherent mononuclear cells (AMCs) derived from the peripheral blood of participants residing in the non-endemic region in the presence of L. infantum promastigotes, with and without antigen-specific IgG and/or CRP. We analyzed the rate of phagocytosis and the production of nitric oxide (NO), tumor necrosis factor (TNF)-a, interleukin (IL)-10, IL-12 p70, IL-1b, IL- 6, and IL-8 in the culture supernatants. Results and discussion In participants from the endemic region, the A/G (H/R isoform) heterozygous genotype was significantly associated with susceptibility to the disease. Furthermore, SNVs induced a change in the phagocytosis rate in an opsonin-dependent manner. Opsonization with IgG increased the production of IL-10, TNF-a, and IL-6 in AMCs with the H/R isoform, followed by a decrease in NO production. The results presented here suggest that the rs1801274 polymorphism is linked to a higher susceptibility to visceral leishmaniasis.